(untitled) (Philologia, 2021)
In this article Professor John Wells provides a ﬁrst-hand, examiner’s experience on how well native speakers of English score in an intonation test which is a part of the practical oral examination in phonetics at the University College London, as in many universities in Britain. The examinees’ performance in the test is discussed in relation to their implementation of the tonality, tonicity and tone in the test sentence. Animated renditions of the test sentence are best avoided and examinees are advised to choose an unmarked intonation pattern in any particular case. The analysis of the examinees’ scores has shown that the safest way to score well in an intonation test is to keep things simple and natural, as intonation in a real language functions this way.